ANALYSIS OF THE DEVELOPMENT OF REGIONAL SOCIO-ECONOMIC CONDITIONS ON THE AGING POPULATION IN ACEH PROVINCE - Al Azizah, Rohil; Mulyani, Wiwik Puji; Sukamdi, Sukamdi (Universitas Airlangga, 2024)
Socio-economic developments in Aceh Province have had a real impact which is reflected in the reduction in death and birth rates as well as an increase in life expectancy, causing changes in the composition of the population aged 60 years and over to increase. However, the developments that have occurred are not evenly distributed throughout the region, it is crucial to be aware of the concept of